Effects of using simulation of micro controller boards student programming achievement two: Kesan penggunaan simulasi papan pengawal mikro terhadap pencapaian pengaturcaraan murid tahap dua - Selvadurai, Eswaran (Jurnal Pendidikan Bitara UPSI, 2023)
Formative assessment, learning for life, student-centered learning, new skills in life and thinking are among the contents of 21st Century Learning (PAK-21) that are important for future generations to face the challenges of the country’s 4IR Policy. There is a practical gap in the widespread use of microcontroller board simulation in the early stages of schooling in Malaysia. Programming and computerbased learning using simulation methods can be an approach for students in primary school. Pupils need problem-solving skill training from an early stage to generate knowledge. The research design conducted is an experimental quantitative study that pays attention to pre-test data and post-test data from the treatment group and the control group. Design and Technology (RBT) students need to be given space or opportunities for different learning according to their efforts to make it easier for themselves to master learning disciplines. This study is relevant considering that there are not many literature studies that have been found focusing on procedures in effective microcontroller simulations in Malaysia.